Bunny - Awad, Mona (Viking, an imprint of Penguin Random House LLC, 2019)
"Samantha Heather Mackey couldn't be more of an outsider in her small, highly selective MFA program at New England's Warren University. A scholarship student who prefers the company of her dark imagination to that of most people, she is utterly repelled by the rest of her fiction writing cohort--a clique of unbearably twee rich girls who call each other "Bunny," and are often found entangled in a group hug so tight they become one. But everything changes when Samantha receives an invitation to the Bunnies' fabled "Smut Salon," and finds herself inexplicably drawn to their front door--ditching her only friend, Ava, a caustic art school dropout, in the process. As Samantha plunges deeper and deeper into the sinister yet saccharine world of the Bunny cult and starts to take part in their ritualistic off-campus "Workshop" where they magically conjure their monstrous creations, the edges of reality begin to blur, and her friendships with Ava and the Bunnies are brought into deadly collision. A spellbinding, down-the-rabbit-hole tale of loneliness and belonging, creativity and agency, and friendship and desire, Bunny is the dazzlingly original second book from an author whose work has been described as "honest, searing and necessary" (Elle)" --